The interaction between resilience framework and neuron-astrocyte-synapse dynamics in AD - Ma, Hongyue; Zhao, Haizhen; Feng, Xinhong; Gao, Fengli (Frontiers in Aging Neuroscience, 2025)
The concept of resilience can be used to explain why there are differences in the degree to which the brain functions of different individuals are impaired due to aging and pathological factors associated with neurodegenerative diseases. It encompasses cognitive reserve, brain reserve, and brain maintenance. Long-term research has identified a default mode network (DMN) related to cognitive reserve. This mode can modulate the negative impact of Alzheimer’s disease (AD) pathological burden on cognitive performance. Meanwhile, the association between neurons and glial cells plays a crucial role in the strength of neural network connections. Glial cells are widely distributed in the brain and interact closely with neurons. Among them, astrocytes are essential for maintaining the normal functions of the central nervous system. In both healthy and diseased states, astrocytes perform a variety of functions, including participating in the regulation of synaptic plasticity, synaptogenesis, maintaining glutamate and ion homeostasis, participating in cholesterol and sphingolipid metabolism, and being able to respond to environmental factors. All of these functions are associated with Alzheimer’s disease. In this review, first, we provided an overview of Cognitive Reserve, Brain Maintenance, and Brain Reserve. Then, we expounded on the possible mechanisms of action related to glial cells. Finally, we described their roles in Alzheimer’s disease and therapeutic development. This review may provide information and relevant therapeutic strategies for future research as well as the design of diagnostic and therapeutic interventions.